2023
DOI: 10.1021/jacs.2c10976
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Oxide–Support Strong Interactions in the Graphdiyne-Supported Cuprous Oxide Nanocluster Catalyst

Abstract: The interfacial interaction in supported catalysts is of great significance for heterogeneous catalysis because it can induce charge transfer, regulate electronic structure of active sites, influence reactant adsorption behavior, and eventually affect the catalytic performance. It has been theoretically and experimentally elucidated well in metal/oxide catalysts and oxide/metal inverse catalysts, but is rarely reported in carbon-supported catalysts due to the inertness of traditional carbon materials. Using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…As illustrated in Figure c, the Raman spectra of both HT and HT/PDDA samples exhibited the same characteristic peaks at 396, 515, and 638 cm –1 , which can be attributed to the B 1g (1), B 1g (2) + A 1g , and E g (3) modes of anatase TiO 2 , respectively . However, these peaks shifted to lower wavenumbers in the HT/PDDA/pGQDs and HT/PDDA/rGQD systems, indicating that the GQDs interacted with TiO 2 , although they were not in direct contact with the semiconductor because of the interfacial PDDA molecules . Moreover, the decreased intensity of the Raman peaks of TiO 2 can be attributed to the capping effect of the GQDs around the TiO 2 substrate.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…As illustrated in Figure c, the Raman spectra of both HT and HT/PDDA samples exhibited the same characteristic peaks at 396, 515, and 638 cm –1 , which can be attributed to the B 1g (1), B 1g (2) + A 1g , and E g (3) modes of anatase TiO 2 , respectively . However, these peaks shifted to lower wavenumbers in the HT/PDDA/pGQDs and HT/PDDA/rGQD systems, indicating that the GQDs interacted with TiO 2 , although they were not in direct contact with the semiconductor because of the interfacial PDDA molecules . Moreover, the decreased intensity of the Raman peaks of TiO 2 can be attributed to the capping effect of the GQDs around the TiO 2 substrate.…”
Section: Resultsmentioning
confidence: 89%
“…31 However, these peaks shifted to lower wavenumbers in the HT/PDDA/pGQDs and HT/ PDDA/rGQD systems, indicating that the GQDs interacted with TiO 2 , although they were not in direct contact with the semiconductor because of the interfacial PDDA molecules. 32 Moreover, the decreased intensity of the Raman peaks of TiO 2 can be attributed to the capping effect of the GQDs around the TiO 2 substrate. Figure S3c displays two broad peaks corresponding to the D and G bands of graphite at 1357 and 1578 cm −1 in pGQDs and rGQDs, 33 which can also be observed in the hybrid systems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…(f) Time-dependent catalyst performance. Reproduced with permission from ref . Copyright 2023, American Chemical Society.…”
Section: Graphdiyne-based Catalytic Materialsmentioning
confidence: 99%
“…Yu et al reported a Cu(I)-catalyzed azide−alkyne cycloaddition reaction by Cu 2 O NCs/GDY (Figure 17a). 154 The charge transfer at the interface stabilized Cu(I) species and optimized adsorption energy for reactants/intermediates (Figure 17b−d), resulting in high performance for a broad scope of substituted acetylenes (Figure 17e−f). Guo and co-workers fabricated the subnanocluster CuO/graphdiyne for an efficient CO oxide (Figure 17g−h).…”
Section: Graphdiyne-based Catalytic Materialsmentioning
confidence: 99%
See 1 more Smart Citation